2017
DOI: 10.1111/ijpp.12376
|View full text |Cite
|
Sign up to set email alerts
|

Tele-pharmacy in rural Scotland: a proof of concept study

Abstract: Community pharmacy services delivered remotely using tele-technology are feasible and acceptable. A larger study should be undertaken to confirm the potential of the TPRSS to reduce health inequalities in rural areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 8 publications
0
15
0
Order By: Relevance
“…Implementation of telepharmacy requires that many important aspects are previously analyzed. Data presented in [9] are the result of a very comprehensive study, and these data and method of analysis may be used as the starting point, when some new telepharmacy system is prepared for initialization. Tested system was installed in one small village in Scotland, i.e.…”
Section: Telepharmacy and The Areas Of Its Implementationmentioning
confidence: 99%
“…Implementation of telepharmacy requires that many important aspects are previously analyzed. Data presented in [9] are the result of a very comprehensive study, and these data and method of analysis may be used as the starting point, when some new telepharmacy system is prepared for initialization. Tested system was installed in one small village in Scotland, i.e.…”
Section: Telepharmacy and The Areas Of Its Implementationmentioning
confidence: 99%
“…There is an excellent report about a tele‐pharmacy pilot study in rural Scotland that served as an excellent proof of concept demonstration. And it should be mentioned that that pilot project has now been installed as part of a routine service in the Scottish highlands with only minor modifications …”
mentioning
confidence: 99%
“…And it should be mentioned that that pilot project has now been installed as part of a routine service in the Scottish highlands with only minor modifications. [4] Canada has suffered a lack of pharmacists, prompting the Canadian government to test the concept of tele-pharmacy in 2003 at a hospital in Cranbrook, British Columbia. The addition of remote dispensing machines happened in Ontario in 2007.…”
mentioning
confidence: 99%
“…Lastly, again in this issue, Inch et al . describe a remote robotic dispensing system linked by video to facilitate prescribing by pharmacists in the minor ailment service in rural Scotland.…”
mentioning
confidence: 99%
“…However, qualitative research involving patients, informal carers, social care staff and pharmacists showed little appetite for being the 'first port of call' for alerts. [15] Lastly, again in this issue, Inch et al [16] describe a remote robotic dispensing system linked by video to facilitate prescribing by pharmacists in the minor ailment service in rural Scotland. Rural practice is facing something of a crisis in terms of attracting clinicians, and such developments will become increasingly important in the future.…”
mentioning
confidence: 99%